1980
DOI: 10.1136/jech.34.2.76
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the health service and environmental factors on infant mortality: the case of Sri Lanka.

Abstract: SUMMARY One of the findings of this study is that regional variations in the infant mortality rates of Sri Lanka are large, ranging from 26 per 1000 live births in Jaffna to 91 per 1000 in Nuwara Eliya, a tea estate district. These differences are more strongly associated with regional variations in environmental determinants of mortality than with regional variations in public health expenditure. The most significant environmental factor associated with interregional infant mortality rates was found to be the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
1
4
0
1
Order By: Relevance
“…The present study of a rural Filipino province augments recent research findings in Sri Lanka (Patel, 1980), Guatemala (Haines et ai, 1983), Costa Rica (Haines & Avery, 1982), and the Philippines as a whole (Martin et ah, 1982) that identify housing quality as a significant factor in child survival. This result implies that policies to improve housing conditions on rural Filipino farms can reduce child mortality more quickly than can policies to raise maternal education or to decrease birth rates among women aged 30+.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present study of a rural Filipino province augments recent research findings in Sri Lanka (Patel, 1980), Guatemala (Haines et ai, 1983), Costa Rica (Haines & Avery, 1982), and the Philippines as a whole (Martin et ah, 1982) that identify housing quality as a significant factor in child survival. This result implies that policies to improve housing conditions on rural Filipino farms can reduce child mortality more quickly than can policies to raise maternal education or to decrease birth rates among women aged 30+.…”
Section: Discussionsupporting
confidence: 86%
“…Little published work has examined housing effects on child mortality in lesser developed countries. Patel (1980) found that regional infant mortality rates in Sri Lanka were inversely related to the percentage of homes with cement floors or with asbestos or tiled roofs. In Costa Rica, Haines & Avery (1982) found that a child's risk of death before exact age 2 years was lower if the mother's dwelling had a latrine and lower still if the home had a sewer or a septic tank.…”
Section: Introductionmentioning
confidence: 98%
“…Analyses that were adjusted for age group, individual azithromycin coverage, and sex also failed to show an association. Despite numerous observational studies that have shown that the presence of latrines is associated with reduced diarrheal morbidity 7,8,[18][19][20][21][22][23][24] and mortality, [25][26][27][28] this cluster-randomized trial was unable to demonstrate a mortality benefit of community latrine promotion. There are several reasons why we may have failed to find an association.…”
Section: Discussionmentioning
confidence: 99%
“…But, before doing that, a brief picture of the current status of the curative systems will be useful (Economic Review 1976Review , 1980. For example, in 1968 two-thirds of all births occurred in hospitals or were supervised at home by a trained midwife (Patel 1980). Any Sri Lankan has available to him, essentially t~ree 1, some sort of government health facility within, on the average, three miles of his home.…”
Section: Current Health Services In Sri Lankamentioning
confidence: 99%